Pengaruh Pendapatan Asli Daerah, Tingkat Kemiskinan, dan Tingkat Pengangguran Terhadap Indeks Pembangunan Manusia (IPM) di Kabupaten Barito Kuala - Nur Asyifa, Rika; Chandriyanti, Ika (PPJP ULM, 2025)
This research aims to determine the influence of the level of local income, the level of poverty, and the level of unemployment simultaneously, partially, and the dominant factors that influence the human development index in Barito Kuala Regency. This type of research is quantitative using secondary data from the Central Statistics Agency of South Kalimantan Province and the Regional Financial and Asset Management Agency of Barito Kuala Regency with a multiple linear regression analysis method of time series data for 2010 - 2022 using e-views 12. The results of the research state that simultaneously, all independent variables have a significant influence on the human development index. Partially, local revenue has a positive and significant effect, the poverty level has a negative and significant effect, while the unemployment rate has a positive but no effect.